Suppression of liver uptake of orally fed liposomes by injection (I.P.) of dextran sulfate 500. Issue 6 (June 1987) - Das, Nirmalendu; Basu, Mukul Kumar; Das, Manoj Kumar
Abstract : 125 Iodine labelled human immunoglobulin-G encapsulated liposomes were administered orally to rats. Distribution of radioactivity was checked in various tissues and in portal blood. The effect of dextran sulfate (DS 500, 000 m. wt., liver blockade agent) injection (i.p.) on the liver uptake of liposomes and on the amount of liposomes appearing in the portal blood from the gastrointestinal tract have been studied. An increased amount of radioactivity was observed in the portal blood and the amount of radioactivity in the liver decreased appreciably after injection of dextran sulfate. In both the cases the action of dextran sulfate started 2 hours after injection and reached maximum at 12 hour, falling slightly at 24 hour.